ASSESSING TEXT ALIGNMENT: SARA MILLS’ MODEL - Ina Sukaesih; Lenny Brida (Epigram, 2017)
This study compares two on-line texts reporting the same news. This study is meant to find out a possibility of the both news alignments seen from the angle of critical discourse analysis of Sara Mills which looks at the perspective of feminism, and the power relations implied in the texts reflected by the words, phrases, and clauses used. This as well studies the accuracy of the equivalence of transferred messages to their source text, and what social and cultural aspects behind the discourse strategy are applied by the authors in the news.   The findings revealed that both the original and the translated news tend to represent woman positively. Seen from the micro features used, woman was positioned proportionally in the texts. Woman does not only take the object position, but also the subject position.  However, some choice of words refers to relatively downgrading which still reflects the man world, especially in the translated version where power relations is clearly influencing. The equivalence of the messages can be considered quite accurate with a discourse strategy of extension. In summary, both texts support gender equality, with some recommendation of a more careful choice of words to attain high equivalence of original message Key words: feminism, gender, equality, power relations, equivalence, discourse strategy